Kacamata Tabu Orang Tua Sebagai Hambatan Pendidikan Seksual Anak Usia Dini - Rasyidin, Ahmad Dimas; Kurniawannafi, Hanasta Rasendriya; Syafira, Luthfia Marselina; Umi, Nabila Farihatul; Chalishah, Siti Nur; Amanda, Viorika; Sulistyorini, Anita (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
Sexual violence against children is a major concern for society. In 2022, 9,588 incidents of sexual violence against early childhood were recorded. This shows that early childhood is a group that is vulnerable to sexual violence. Sex education is an important part of early childhood development. However, many parents avoid this topic with their children because it is taboo, hindering early childhood sex education. Therefore, this study aims to find out the differences in perceptions or taboo views of parents regarding sex education and the reasons it hinders early childhood sex education. This study uses a literature review approach by analyzing 11 articles that discuss parents' taboo views on sex education in early childhood. Based on the results of the analysis, most parents consider sex education important, but not urgent, feel uncomfortable and lack a clear understanding of how to convey sex education to children, consider sex to be equivalent to teaching children about sexual behavior. Therefore, efforts need to be made to improve parents' understanding of sex education in preschool children. Parents need to understand that sex education doesn’t teach children about having sex, but helps children understand their bodies, gender identity, and healthy behavior depending on their age.